Grey Owl - Attenborough, Richard; Brosnan, Pierce; Galipeau, Annie; Bick, Stewart (Santa Monica, CA : Lionsgate, 2011)
A 1930s frontier trapper adopts the ways of the native people in his area and fights for the protection of the land he loves.
Originally released as a motion picture in 1999.
Features: biographies and filmographies, behind-the-scenes interviews, shorts on the real Grey Owl.
Pierce Brosnan, Annie Galipeau, Stewart Bick, Vlasta Vrana, Neil Kroetsch.
MPAA rating: PG-13.
DVD, Dolby digital 5.1 surround.
In English with optional English or Spanish subtitles.
Keywords: Grey Owl, -- 1888-1938 -- Drama; Conservationists -- Canada -- Drama; Canada -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films; Biographical films; Historical films